Identificação e comportamento da feminização da pobreza no Brasil e no México (2000 – 2010) - Guarda, Évelyn Taiuane Sonnenstrahl (2023)
The feminization of poverty is commonly discussed in terms of a comparison between female poverty and male poverty. However, the Institute of Applied Economic Research (IPEA) (2005) identified this phenomenon as the overrepresentation of poverty. The feminization of poverty is identified independently of male variation, as it refers to the increase of women in poverty rates regardless of men. Using a comparative method, this research aims to identify the feminization of poverty and its behavior between the years 2000 and 2010 in two strong Latin American states: Brazil and Mexico. The hypothesis presented is that there was feminization of poverty in both countries, regardless of poverty reduction, and that there is at least overrepresentation (more poor women than men). The independent variables in this research are: gender inequality, reflecting a patriarchal political structure; and neoliberalism, which acts as the economic and political backdrop of the states under analysis. The intervening variables, which act as intensifying agents of the problem, are: unemployment, as it constitutes the worst situation for the working class; informality, as the lack of rights and the dependence on precarious work make it difficult to escape poverty; female household headship, as women earn lower wages and have a dual work burden, resulting in inequalities when compared to households where the primary source of income comes from a man; and race/ethnicity, due to the racist legacy against black and indigenous people, combined with patriarchy that marginalizes women, especially black and indigenous women. Finally, the dependent variable is the feminization of poverty itself because it is the condition found. It is considered that within a neoliberal scenario, gender inequality, acting through the labor market, conditions more women to poverty. In the 2000s, Brazil and Mexico went through a period of political change; however, they share the same agenda: neoliberalism. The more conservative step taken by Mexico with Felipe Calderón coming to power differs from the leftward turn with Luiz Inácio Lula da Silva elected as the president of Brazil. The analysis conducted in this research highlights the existence of gender inequality, the invisibility of data with gender/ethnicity breakdown, and that poverty affects men to a greater extent. In order to identify the feminization of poverty, the theoretical agents addressed are gender and poverty. The historical analysis of the politics and economy of both states is carried out in order to represent the scenario in which the feminization behavior is analyzed. Finally, the empirical data analyzed are the intervening variables considered as potential agents in the process of feminization of poverty.